Learning experiences in community health of nursing students - Gladys Carmela Santos Falcón; Santa Dolores Torres Alvarez; Luz Elena Capcha Caso; Gladys Filomena García Arias; María Virginia Infante Contreras; Alacoque Lorenzini Erdmann
ABSTRACT Objective: Understand the learning experiences on health promotion and prevention of nursing interns during their community practice. Method: This is a descriptive-interpretative study, with a qualitative approach, obtaining data from 19 nursing interns from a public university in Lima-Perú, using 3 focus groups. Results: Three categories were structured: considering the importance of the nursing teacher in their training; experiencing complexity in training for the prevention and promotion of health in the community; and considering the preventive-promotional area as a future professional practice. Final Considerations: The students perceived the complexity of community practice in the prevention and promotion of health. They stated that teachers and students should know the context where they develop their practices and that teacher's exercise leadership in the community. The inclination of some nursing interns for their future professional practice in this area was also evident.